2013
DOI: 10.3109/09553002.2013.802394
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of hypocoagulability in proton-irradiated ferrets

Abstract: Purpose To determine the mechanism of proton radiation-induced coagulopathy. Material and methods Ferrets were exposed to either solar particle event (SPE)-like proton radiation at a predetermined dose rate of 0.5 Gray (Gy) per hour (h) for a total dose of 0 or 1 Gy. Blood was collected pre- and post-irradiation for a complete blood cell count or a soluble fibrin concentration analysis, to determine whether coagulation activation had occurred. Tissue was stained with an anti-fibrinogen antibody to confirm th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
0
19
1
Order By: Relevance
“…A reduction in the number of platelets can result in hemorrhaging and death; however, our results in irradiated ferrets suggest that a reduction in the number of platelets does not cause the blood clotting abnormalities leading to DIC after radiation exposure (3, 4). We have reported that platelet cell counts in ferrets exposed to a 1 Gy dose of SPE proton radiation are not significantly different from control levels over 7 days postirradiation.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…A reduction in the number of platelets can result in hemorrhaging and death; however, our results in irradiated ferrets suggest that a reduction in the number of platelets does not cause the blood clotting abnormalities leading to DIC after radiation exposure (3, 4). We have reported that platelet cell counts in ferrets exposed to a 1 Gy dose of SPE proton radiation are not significantly different from control levels over 7 days postirradiation.…”
mentioning
confidence: 53%
“…Ferrets exposed to SPE radiation have increased clotting times and factor deficiencies, indicating hypocoagulability (3). Our current studies in ferrets have shown that SPE proton radiation exposure at 1 Gy leads to increased bleeding times, concentrations of soluble fibrin in blood, and fibrin clotting in the livers, lungs and kidneys of irradiated ferrets within 24 h postirradiation (3, 4). The measurement of soluble fibrin in the blood is a marker for DIC in the clinic (5).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…We have hypothesized that the SPE-like proton irradiation activates the coagulation cascade, which would put irradiated subjects in a hypocoagulable state. To test this hypothesis, a separate experiment was performed with 12 to 15 week old de-scented female ferrets irradiated with 1 Gy of 110-MeV protons at a dose rate of 0.5 Gy/hour, and the results indicate that the radiation exposure resulted in coagulation cascade activation, which was indicated by increases in soluble fibrin concentration in the blood and fibrin clots in blood vessels of livers, lungs and kidneys from irradiated ferrets (208). The soluble fibrin concentration was determined using a rapid soluble fibrin assay that was previously developed and implemented at the Loma Linda University Medical Center to aid in early detection of DIC in emergency room, operating room, or transplant patients (209).…”
Section: Acute Radiation Effectsmentioning
confidence: 99%
“…6 Animal experiments in minipigs 60 suggest that the RBE for acute radiation syndrome of protons in simulated SPE is .1. Ferrets exposed to SPE-like protons had increase in fibrin clots, prothrombin time and partial thromboplastin time values post-irradiation, 61 suggesting a proton radiation-induced coagulopathy, which represents a risk for SPE in space but may find important applications in CPT.…”
Section: Hypofractionationmentioning
confidence: 99%